Task independence in stated preference studies: A test of order effect explanations - Brett Day; Ian J. Bateman; Richard T. Carson; Diane Dupont; Jordan J. Louviere; Sanae Morimoto; Riccardo Scarpa; Paul Wang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2009)
We present an experiment designed to investigate the presence and nature of ordering effects within repeated response stated preference studies. We formulate a general structural model of such effects and use this to isolate signature patterns for position-dependent effects (learning about preferences or institutions, and the impact of fatigue) and precedent-dependent effects (starting point effects, reference pricing and various forms of strategic behavior). This is tested within a large sample, full factorial study designed to mitigate against misspecification bias and design-induced error variance problems. Non-parametric and parametric analyses are applied, the latter adopting a novel data-driven approach to the detection of ordering patterns. While we find little evidence of position dependent effects, we do find evidence of a starting point effect and various types of strategic behavior including a reference price effect where respondents tend to reject alternatives that are priced higher than recently seen alternatives.
Keywords: 330; Stated preference; ordering effect; strategic behavior; reference price; drinking water; Offenbarte Präferenzen; Strategie; Verhaltensökonomik; Öffentliches Gut; Test; Experimentelle Ökonomik